Push Notification Using Firebase Cloud Messaging (FCM) on Employee Attendance Application - Abdussalam Abdussalam; Bayu Wicaksono; Ajib Susanto; Sudaryanto Sudaryanto (SISFOTENIKA, 2021)
The attendance system uses a tool called a fingerprint like a developing technology, if there is a new technology that is old, it will show its shortcomings, namely making long queues at the time of attendance, having to come to the place of absence, and requiring processing for real time notifications, plus at this time during the Covid-19 pandemic which requires employees to work from home (WFH). The purpose of this study is to produce an android-based attendance system that can be installed on all employees' android phones using Firebase Cloud Messaging (FCM) for real time notification features that will appear on the android phones of the dept heads and staff who use it. This study uses a prototyping system development method with a sequence of stages: needs analysis, design, prototype making, prototype evaluation, testing, implementation, and maintenance. The results of the notification application test successfully appear on the employee side and on the leadership side in the process of applying for leave or permission either approved or rejected on employees' android phones without having to open the application first and this application can be accessed anywhere and anytime to process permits or leave employees and provide real time notifications.